2019
DOI: 10.1101/811380
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic encoding of social threat and spatial context in the hypothalamus

Abstract: 14Territorial animals must be able to express social aggression or avoidance in a manner 15 appropriate to spatial context and dominance status. Recent studies indicate that the 16 ventromedial hypothalamus controls both innate aggression and avoidance, suggesting that it 17 may encode an internal state of threat common to both behaviors. Here we used single unit in 18 vivo calcium microendoscopy to identify neurons in the mouse ventromedial hypothalamus 19 encoding social threat. Threat neurons were activated… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Our findings have two important implications for our understanding of fear in humans. First, our discovery makes it likely that the medial hypothalamus plays a similar role in encoding an internal state of threat in primates as it does in rodents (Kunwar 2015;Silva et al 2016a;Esteban Masferrer et al 2018;Krzywkowski et al 2019;Masferrer et al 2018;Kennedy et al 2019). Notably, VMHdm in rodents is required for the induction and expression of both innate and conditioned predator fear (Silva et al 2013(Silva et al , 2016Kunwar 2015) and stimulation of VMHdm in monkeys and humans is sufficient to elicit an intense defensive emotional state (Wilent 2010;Lipp and Hunsperger 1978).…”
Section: Discussionmentioning
confidence: 95%
“…Our findings have two important implications for our understanding of fear in humans. First, our discovery makes it likely that the medial hypothalamus plays a similar role in encoding an internal state of threat in primates as it does in rodents (Kunwar 2015;Silva et al 2016a;Esteban Masferrer et al 2018;Krzywkowski et al 2019;Masferrer et al 2018;Kennedy et al 2019). Notably, VMHdm in rodents is required for the induction and expression of both innate and conditioned predator fear (Silva et al 2013(Silva et al , 2016Kunwar 2015) and stimulation of VMHdm in monkeys and humans is sufficient to elicit an intense defensive emotional state (Wilent 2010;Lipp and Hunsperger 1978).…”
Section: Discussionmentioning
confidence: 95%
“…This finding has two important implications for our understanding of fear in humans. First, our discovery makes it likely that the medial hypothalamus plays a similar role in encoding an internal state of threat in primates as it does in rodents (10,21,3032). Notably, VMHdm in rodents is required for the induction and expression of both innate and conditioned predator fear (8,10,21) and stimulation of VMHdm in monkeys and humans is sufficient to elicit an intense defensive emotional state (11,33).…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Extensive work has been carried out on a central node in this system, the ventromedial hypothalamus (VMH), and inhibition of this nucleus blocks defensive responses to predator and social threats, [7,8] while activation elicits flight behavior. [8][9][10][11][12][13] Consistent with its anatomical conservation between rodents and primates [5,12] electrical stimulation of VMH in humans elicits intense arousal, negative emotion, and panic, [14] supporting the hypothesis that VMH encodes an internal defensive state that is relevant to understanding instinctive fear in humans. [15] In vivo single unit electrophysiology and calcium endoscopy recordings in freely behaving mice have revealed that VMH encodes both sensory and motor features of defensive behavior.…”
Section: Introductionmentioning
confidence: 91%
“…[15] In vivo single unit electrophysiology and calcium endoscopy recordings in freely behaving mice have revealed that VMH encodes both sensory and motor features of defensive behavior. [10,16] Single unit electrophysiology recordings were carried out in VMH as mice approached and then fled a live rat, a natural predator. Twenty-eight percent of units showed significant changes in firing during the approach-to-flight behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation